2022
DOI: 10.1002/essoar.10511565.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Destructive potential of planetary meteotsunami waves beyond the Hunga volcano eruption (Tonga)

Abstract: Worldwide tsunamis generated by atmospheric waves -or planetary meteotsunami waves -are extremely rare events occurring during supervolcano explosions or asteroid impacts. Recently, such waves have been globally recorded after the Hunga volcano eruption (Tonga) but did not pose any serious danger to the coastal communities. However, this study highlights that the mostly ignored destructive potential of planetary meteotsunami waves can be compared to the well-studied tsunami hazards. Through simple numerical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The numerical simulations carried out by Refs. 21 , 22 show that waves of a few cm were generated in the open ocean during the passage of the atmospheric disturbance. The simulations also show that these waves were organized in several wave fronts, since when the atmospheric wave overtakes the ocean waves the latter are decoupled and travel at a lower speed as tsunami waves 16 , 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The numerical simulations carried out by Refs. 21 , 22 show that waves of a few cm were generated in the open ocean during the passage of the atmospheric disturbance. The simulations also show that these waves were organized in several wave fronts, since when the atmospheric wave overtakes the ocean waves the latter are decoupled and travel at a lower speed as tsunami waves 16 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…19 tried to relate the timings and amplitudes recorded by tide gauges located worldwide with the different generating processes outlined above; however, they did not examine in detail the causes of the observed spatial heterogeneity. Other works have performed global numerical simulations of the atmosphere-ocean coupling that resulted in the ocean long waves observed outside the Pacific Ocean 21,22 ; however, these studies cannot reproduce the sea level oscillations observed by coastal tide gauges, because this would require high resolution simulations with very high-resolution bathymetries near the coast (which is prohibitive for global-scale simulations).Here we try to explain the spatial heterogeneity of the observed sea level response at the coast through an exhaustive analysis of atmospheric pressure and sea level observations recorded worldwide. On one hand, we intend to give an overall description of the observations to highlight the global dimension of both, the atmospheric pressure disturbance and the sea level response.…”
mentioning
confidence: 99%
See 1 more Smart Citation